Applying Natural Language Processing Capabilities in Computerized Textual Analysis to Measure Organizational Culture. (July 2019) - Pandey, Sheela; Pandey, Sanjay K.
We build on and extend methodological developments in computerized textual analysis and apply it for developing and validating a measure for the widely used concept of organizational culture. Although the organizational culture concept is widely used in a variety of domains of management scholarship, its measurement is primarily based on survey questionnaires. In this study, we extend computerized textual analysis by introducing the capabilities of natural language processing (NLP). NLP capabilities are artificial intelligence techniques for textual analysis that make it possible to conduct textual analysis at the multiple word level. We follow recommendations for establishing construct validity and demonstrate that the measure of organizational culture dimensions outlined in the study has content validity, external validity, dimensionality, and predictive validity.